The Influence of Ethical Climate on The Organizational Commitment of Nurses in Government Hospitals in Padang, Indonesia - Sidaria, Sidaria; Fahmy, Rahmi; Merdawati, Leni (LPPM Universitas Ekasakti, 2025)
Commitment of nurses to hospitals remains a challenge in human resource management. One factor influencing organizational commitment is ethical climate, an individual's perception of values, norms, and moral standards in the work environment. A positive ethical climate is believed to increase nurses' loyalty and emotional attachment to the institution. This study aims to analyze the effect of ethical climate on organizational commitment among nurses in government hospitals in Padang City, Indonesia. This is a quantitative explanatory study with a sample of 69 nurses who met the inclusion criteria, taken by proportional random sampling. Data were collected using a questionnaire and analyzed with SmartPLS. The results showed a significant positive effect of the ethical climate of benevolence and principles (caring, independent, law and code, rules) on organizational commitment (T-statistic 7.715; P value 0.000; sample mean 0.745, R square 0.440), and there was no effect of instrumental climate on organizational commitment. A positive ethical climate that reflects caring, compliance with rules, and the principle that every action and decision is based on personal or professional standards can strengthen nurses' commitment to the organization. Strengthening ethical culture is important in building sustainable and quality-oriented health services.